2012
DOI: 10.1111/j.1475-6773.2011.01376.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect ofHIFA Waiver Expansions on Uninsurance Rates in Adult 
Populations

Abstract: Research Objective. To evaluate the effect of the Health Insurance Flexibility and Accountability (HIFA) demonstrations on the rate of uninsured. The policy purpose of the HIFA demonstrations is to encourage "new comprehensive state approaches" that will increase the number of insured. HIFA interventions include changes in benefit packages, eligibility rules for public programs, and state subsidization of private health insurance premiums. Some states emphasized private insurance (premium assistance), whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…Lawler 2005; Gardner 2008; Frenk 2006; Currie 1996; Bitran 2010; Long 2007; Cousineau 2011; Lo Sasso 2004; Hill 1993; Gresenz 2012; Card 2004; Buratto 2004; and Buchmueller 2008 had post-intervention descriptions without controls. In addition, there were before-after studies (Cogan 2008; Kenney 2010; Meyer 2004; Prado 2010; Shore-Sheppard 2000; Souares 2010; Thornton 2010), retrospective studies (Atherly 2012; Barnett 2010; Bowblis 2008; Choi 2011), time series (Dave 2010; Guy 2010; Zimmer 2011), CBA (Sieben 2000), a cluster-RCT (Chen 2009), and a case control study (Leininger 2007). These studies could not control for some confounding factors.…”
Section: Resultsmentioning
confidence: 99%
“…Lawler 2005; Gardner 2008; Frenk 2006; Currie 1996; Bitran 2010; Long 2007; Cousineau 2011; Lo Sasso 2004; Hill 1993; Gresenz 2012; Card 2004; Buratto 2004; and Buchmueller 2008 had post-intervention descriptions without controls. In addition, there were before-after studies (Cogan 2008; Kenney 2010; Meyer 2004; Prado 2010; Shore-Sheppard 2000; Souares 2010; Thornton 2010), retrospective studies (Atherly 2012; Barnett 2010; Bowblis 2008; Choi 2011), time series (Dave 2010; Guy 2010; Zimmer 2011), CBA (Sieben 2000), a cluster-RCT (Chen 2009), and a case control study (Leininger 2007). These studies could not control for some confounding factors.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, between 2001 and 2007 about 24 states have utilized section 1115 demonstrations to increase Medicaid enrollment by expanding eligibility for state-sponsored health insurance (Coughlin and Zuckerman 2008). A recent study estimated the effects of some of these waivers and found that such waivers significantly increased insurance coverage among the targeted population (Atherly et al 2012). More recently, in 2011 California and six other states used a section 1115 waiver to provide Medicaid eligibility to all low-income adults below 138 percent of the FPL.…”
Section: B I N S T R U M E N T Smentioning
confidence: 99%
“…HIFA allowed states more flexibility in restructuring their Medicaid and Children’s Health Insurance Program (CHIP) and creating incentives for states to expand insurance coverage to adults with incomes less than 200 percent of the Federal Poverty Level (FPL) . Studies have shown that states that implemented a Section 1115 waiver reduced the proportion of their residents without health insurance …”
Section: Introductionmentioning
confidence: 99%